Review of application of biomimetics for designing soil-engaging tillage implements in Northeast China - Zhijun, Zhang; Honglei, Jia; Jiyu, Sun (International Journal of Agricultural and Biological Engineering, 2016)
The reduction of water resources and soil fertility in Northeast China will have a requirement on higher working efficiency of agricultural soil-engaging components. The adhesion and resistance are main problems for soil-engaging tillage components. However, the soil-burrowing or soil-digging animals give inspirations to resolve those problems. Their fair, claw, toe, textured surface and scales have functions of anti-adhesion or resistance reduction. Those results provide a way to realize the sustainable development of modern agriculture by developing novel biomimetic agricultural machinery systems with independent intellectual property rights to meet conservation tillage requirements in the Northern China region. Biological structures of some soil-burrowing or soil-digging animals, such as beetle, mole cricket, earthworm, mole, vole, pangolin, and snake, as well as their mechanisms of anti-adhesion or reducing resistance were reviewed in this paper. Bioinspired applications in Northeast China were also presented in the paper, including moldboard, subsoiler components, furrow opener, roller, and biomimetic rototilling-stubble-breaking blade. In addition, the existed problems in agricultural engineering and the future development trends were discussed.Keywords: review, agricultural engineering, biomimetics, soil-engaging tillage implements, conservation tillageDOI: 10.3965/j.ijabe.20160904.1437Citation: Zhang Z J, Jia H L, Sun J Y. Review on application of biomimetic for designing soil-engaging tillage implements in Northeast China. Int J Agric & Biol Eng, 2016; 9(4): 12－21.